Pelaksanaan Pengalihan Kewenangan Pengelolaan Sekolah Menengah Atas/Kejuruan dari Pemerintah Kabupaten ke Pemerintah Provinsi (Studi Kasus Di SMKN 2 Sumbawa Besar) - Syaifuddin Iskandar; Sri Nurhidayati; Saiful Anwar; Muhammad Salahuddin (Indonesian Publication Center, 2020)
The authority in managing SMK / SMA which was originally in the district/city government has now transferred to the provincial government, including SMKN 2 Sumbawa Besar. Although a representative office of the provincial government lies in Sumbawa Regency, in this case, the Education Branch Office (KCD), but all of the administrative matters are complicated. This research used a qualitative method. Interviews, observation, and documentation techniques conducted in collecting the data. Data analysis applied the interactive analysis method of Miles and Huberman. The results showed that the implementation of the management authority transfer of SMK Negeri 2 Sumbawa Besar through several steps that have been taken such as coordination, socialization, and synergy carried out together with other related parties, the inventory stage, the implementation stage of the handover starts from personal handover, submitting infrastructure or assets, submission of budgets and documents. However, after all of the process, several problems emerged include the convoluted procedures and processes in administrative management, the out of sync data and several other findings.